Eliminating voids and reducing mechanical anisotropy in fused filament fabrication parts by adjusting the filament extrusion rate. (August 2022) - Ghorbani, Jafar; Koirala, Pratik; Shen, Yu-Lin; Tehrani, Mehran
Abstract: Fused filament fabrication (FFF) is one of the most common additive manufacturing (AM) processes due to its simplicity and low cost. However, weak interlayer interfaces, high porosity, and mechanical anisotropy limit FFF applications. This paper investigates the effects of an FFF process parameter, i.e., extrusion multiplier, on the structure and interlayer strength of FFF parts made from acrylonitrile butadiene styrene (ABS). Increasing the extrusion multiplier over its predefined standard value improved the tensile strength in the print direction (X-orientation) and build direction ( Z -orientation) by up to 10% and 50%, respectively, resulting in entirely void-free parts with nearly isotropic strength. These improvements are explained via finite element analysis (FEA) and bonding mechanisms in FFF. Finally, the effects of extrusion rate on various AM features in a benchmark part are investigated. This study shows that mechanical anisotropy is not inherent to FFF and, despite the common belief, voids can be eliminated entirely in FFF parts. Complex isotropic parts can be made via FFF, opening new applications for this technology and allowing it to compete with other AM processes. Graphical abstract: Unlabelled Image